Crohn's disease and skin. Issue 2 (1st April 2016) - Gravina, AG; Federico, A; Ruocco, E; Lo Schiavo, A; Romano, F; Miranda, A; Sgambato, D; Dallio, M; Ruocco, V; Loguercio, C; Romano, M
Abstract : Crohn's disease is a chronic inflammatory bowel disease potentially involving any segment of the gastrointestinal tract. Extra‐intestinal manifestations may occur in 6%–40% of patients, and disorders of the skin are among the most common. This manuscript will review skin manifestations associated to Crohn's disease, with a particular focus on lesions associated to anti‐tumour necrosis factor therapy.